THE TEACHING WRITING OF DESCRIPTIVE TEXT IN SPECIFIC CLASS OF THE SEVEN GRADE OF MTSN 2 KEDIRI - Ramadhany, Damara Ilham; Amroni, Agus (Jurnal Pendidikan Bahasa Inggris Proficiency, 2019)
This research was carried out to answer the 3 objectives of study. Those are: (1) the teaching process in 7C class (in the terms of curriculum, syllabus, lesson plan, method, and media), (2) the response student (in term dificulties, perception) and (3) the teacher solution (in the terms of Problem indication and problem solving). The design was descriptive qualitative. The reason of this study used descriptive qualitative because the teaching writing of descriptive text in specific class of MTsN 2 Kediri was so unique because teacher use blog as media to support learning activities. The research instruments were observation sheet, interview note/sheet, document, and field note. The data collecting method were observation, interview, documentation, and field note. The data analysis descriptively using data reduction, data display, verification, and the validity of triangulation. The findings were 1) The teaching process was had Syllabus, Lesson plan, method, and media, 2) The response of student towards the teaching and learning process writing class is good. 3) The problem solution done by teacher is always reminding and evaluating the mistakes made by student. Based on the findings above the teaching writing of descriptive text was good because teacher maximaly media and the other were also maximal and appropriate.